Does language fashion perceptions? - Chen, Kangxing. (2008)
The additional choice of language in marketing, that follows the proliferation of international commerce, triggers off an inspection on which language elicits a more favourable outcome for marketing communications. When Chinese-English bilinguals were asked to respond to different language cues, the study shows that language does indeed evoke varying attitudes.